Rabies infection in a dog with pathogenic virus in salivary gland and non-infective virus in the brain - Silva, Renato Augusto da; Silva, Norma Moraes da (Pesquisa Agropecuaria Brasileira, 2014)
This paper reports a case study of rabies in a domestic dog. Diagnoses of rabies were made in the laboratory by the fluorescent antibody technique, the detection of Negri bodies and mouse innoculation. The presence of the rabies viral antigen in the brain, cerebellum and salivary glands of the dog was shown by the fluorescent antibody technique. The rabies virus was isolated from the salivary glands but not from the central nervous system, by the mouse inoculation technique.